1991
DOI: 10.1159/000200662
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel Blockers Alter Slow-Wave Frequency of the Rat Stomach in vivo

Abstract: Treatment with sodium-channel-blocking agents is accompanied by a high incidence of gastrointestinal side effects. We therefore studied the influence of two sodium channel blockers, mexiletine and flecanaide, on gastric and jejunal myoelectrical activity of unanesthetized rats. Bipolar electrodes were implanted chronically on the serosal surface of the antrum or the jejunum of male rats (weight: 250–350 g). Electrical activity was recorded on a Polygraph starting on day 5 after the operation. After 1 h of base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Another sodium channel blocker, mexiletine, effectively blocked inward sodium current responsible for depolwization of the cardiac action potentids (Yatani and Akaike 1985;Hering et al 1983). In the gastrointestinal tract, an in viva investigation r e v d d that mexiletine reduced gastric, but not Jejunal, slow wave frequency (Bielefeldt and Bass 1991). In the rnouse s d l intestine we observed that mexiletine did not alter the slow wave.…”
Section: Effwts Of Npg Flolfenmic Acid and Gadoliniummentioning
confidence: 49%
“…Another sodium channel blocker, mexiletine, effectively blocked inward sodium current responsible for depolwization of the cardiac action potentids (Yatani and Akaike 1985;Hering et al 1983). In the gastrointestinal tract, an in viva investigation r e v d d that mexiletine reduced gastric, but not Jejunal, slow wave frequency (Bielefeldt and Bass 1991). In the rnouse s d l intestine we observed that mexiletine did not alter the slow wave.…”
Section: Effwts Of Npg Flolfenmic Acid and Gadoliniummentioning
confidence: 49%
“…RR were resampled and interpolated at a rate of 64 Hz to provide continuity in the time domain. Raw tracings of EGMG activity were inspected visually to verify the presence of gastric slow wave and to determine its frequency by calculating the number of slow wave activity during a random 10‐min period in each sleep–wake state (Bielefeldt and Bass, 1991). The provisional slow wave frequency was used as a reference in defining the EGMG frequency during subsequent power spectral analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that there is baseline flow of Na + through Na v 1.5 and that this flow is altered by mechanical forces applied to the cells that express Na v 1.5 whether in the human gut or heart. The Na + channel blockers decrease gastric slow wave frequency in vivo in unanaesthetized rats 50 . Pharmacological blockade of the Na + current in intestinal muscle strips decreases slow wave frequency and hyperpolarizes smooth muscle.…”
Section: Calcium Channelsmentioning
confidence: 99%